Bay' Mumtalakat Al-waqf: Dirasah Tahliliyah Fi Dau' Tashri'at Al-waqf Fī Hukumah Maliziya - Muhamad Firdaus Ab Rahman; Hussein 'Azeemi Abdullah Thaidi; Mohammad Naqib Hamdan; Siti Farahiyah Ab Rahim (Faculty of Shariah and Law, Syarif Hidayatullah State Islamic University Jakarta, 2024)
Indexed by SCOPUS